Avaliação da atividade biológica in vitro de triazenos, sertralina e metildopa como alternativas no reaproveitamento de medicamentos - Bottega, Angelita (2021)
Currently, countless efforts to discover effective, selective and innovative antineoplastic and antimicrobial therapies have led to the synthesis and investigation of the biological activity of different molecules. Triazenes (TZCs) have established themselves as a promising class for drug discovery due to the wide pharmacological versatility demonstrated. Another approach is the reuse of medications, that is, investigating new uses for drugs already clinically approved in the treatment of other diseases. This practice has proven to be a good alternative, since it reduces risks, time and costs associated with the clinical development process, due to the availability of known pharmacokinetic and toxicological data. Our research group has evaluated the pharmacological potential of a series of triazene compounds and different drugs used in clinical practice, as alternatives in redirecting. We report the in vitro biological activity evaluation of three N-óxide triazene molecules: M1 (3- (4-chlorophenyl) -1-phenyltriazene N1-óxide), M2 (3- (4-bromophenyl) -1-phenyltriazene N1-óxido ) and M3 (3- (4-iodophenyl) -1-phenyltriazene N1-óxide), three N-óxide triazenide complexes of Cu(II): C1 ({Bis [3- (4-chlorophenyl) -1-phenyltriazenide N1- óxide-κ2N1, O4] copper (II)}), C2 ({Bis [3- (4-bromophenyl) -1-phenyltriazenide N1-oxido-κ2N1,O4]copper(II)}) and C3 ({Bis [3 - (4-iodophenyl) -1-phenyltriazenide N1-óxido-κ2N1, O4]copper (II)}) and their respective precursors, P1 (4-Chlorophenyl-amine), P2 (4-Bromophenyl-amine) and P3 (4-Iodophenyl-amine), as well as the candidate drugs for redirection, sertraline and methyldopa. The antibacterial activity was determined by the broth microdilution method, through the evaluation of minimal inhibitory concentration (MIC), against strains of the American Type Culture Collection and multidrug-resistant clinical isolates (MDR). Cytotoxicity was investigated using cell line cultures (tumor: murine melanoma - B16F10, human hepatocarcinoma - HepG2, glioblastoma multiforme - U87MG and T98G; normal: 292T - embryonic kidney fibroblast) using the colorimetric assay with the bromide reagent 3-(4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium (MTT). The chemical nuclease activity was verified using the agarose gel electrophoresis technique. The tested compounds showed variable cytotoxic activity. The C3 complex showed a greater cytotoxic effect compared to the HepG2 (IC50 = 2.672 μM) and B16F10 (IC50 = 3.950 μM) lines, being more active than the standard sorafenib tosylate (nexavar® - Bayer) (IC50 = 7,133 μM) and temozolomide (temodal® - Schering-Plow) (IC50 = 8,402 μM), respectively. In the strains of glioblastoma multiforme, the free N-óxide molecules were more cytotoxic compared to U87MG, with M1 (IC50 = 1.488 μM) with greater activity, which was approximately three times more active than standard temozolimide chemotherapy (IC50 = 4.369 μM). In relation to T98G, the N-óxide triazenide complexes showed a greater cytotoxic effect, highlighting the activity of the C2 complex (IC50 = 9.211 μM), whose values were close to that presented by the temozolomide standard (IC50 = 7.326 μM). The TZCs showed antibacterial activity, being more active compared to Gram positive. These did not show nuclease activity, as they were not able to cleave plasmid DNA. Among the drugs, sertraline showed greater antibacterial activity than methyldopa, both against Gram positive and Gram negative strains. However, additional studies are needed to evaluate the mechanisms of action involved to make its use safe in the treatment of infectious diseases of bacterial origin. Synergistic events (FICI <0.5) occurred between sertraline and methyldopa and in their associations with sulfamethoxazole/ trimethoprim. Methyldopa has chemical nuclease activity because it was able to cleave plasmid DNA, by a probable mechanism of hydrolytic action, similar to that promoted by natural nucleases. We conclude that the tested TZCs, M1 and C3, as well as the redirected drugs sertraline and methyldopa demonstrate an alternative for the design of new drugs with antitumor and antibacterial properties.